Marketing: Analisis pasar untuk instansi pendidikan dasar - Uliya, Nurul Manzilatul (Maliki Interdisciplinary Journal, 2024)
Basic education is the main foundation in the formation of quality individual and community potential. Efforts to improve basic education services require a deep understanding of the surrounding market dynamics. This research aims to conduct a comprehensive market analysis of basic education institutions, explore the factors that influence consumer decision making, and assess market needs and expectations regarding educational services. The research methods used include surveys, interviews, and analysis of primary and secondary data to obtain detailed information regarding consumer preferences, educational trends, and competition in the basic education environment. The collected data is analyzed quantitatively and qualitatively to understand market characteristics, look for service development opportunities, and that can be implemented by educational institutions to increase competitiveness and relevance in facing changing market dynamics. It is hoped that the results of this analysis will provide a clearer view of the needs of the basic education market, enable educational institutions to adapt their programs, improve the quality of services, and expand reach to accommodate existing challenges and opportunities. This research contributes to a better understanding of the importance of market analysis in the context of basic education, as well as providing a basis for strategic decision making in improving the effectiveness and efficiency of education services.